Learning Assessment Techniques for Islamic Religious Education Curriculum 2013 - Rizal Fathurrohman; Elvi Tri Astuti Rahmah; Andi Prastowo (Journal of Islamic Education Research, 2023)
The purpose of this study is to describe the various skills evaluation techniques used in Islamic education learning, as well as their advantages and disadvantages by using the library research method. Skills assessment is the value given to students according to their capacity to apply knowledge and carry out tasks according to the specified indicators. Assessment of abstract skills and assessment of actual skills are two categories in which skills are evaluated based on qualitative inquiry findings and documentation as sources. This project is simpler because it affects students' critical thinking skills when the findings of the multiple skills test study are compared with performance, product, and portfolio. However, each type of skill assessment has its advantages and disadvantages. The greatest benefit is that, when compared to tests, all four are equally reliable in determining student aptitude. In addition to the benefits, there must also be disadvantages. Of the four, the time limit is the most important. When evaluating student talent through performance, products, projects, and portfolios, teachers must spend a lot of time. Therefore the teacher must be extra careful in assessing student competence because it is done continuously.